NEGATIVE REGULATION OF MEMORY PHENOTYPE CD8 T CELL CONVERSION BY ADHESION AND DEGRANULATION PROMOTING ADAPTER PROTEIN (ADAP)() - Fiege, Jessica K. (J Immunol, 2015)
The maintenance of T cell repertoire diversity involves the entry of newly developed T cells, as well as the maintenance of memory T cells generated from previous infections. This balance depends on competition for a limited amount of homeostatic cytokines and interaction with self-peptide MHC-I. In the absence of prior infection, memory-like or memory phenotype (MP) CD8 T cells can arise from homeostatic cytokine exposure during neonatal lymphopenia. Aside from downstream cytokine signaling, little is known about the regulation of the conversion of naïve CD8 T cells to MP CD8 T cells during acute lymphopenia. We have identified a novel negative regulatory role for the adapter protein ADAP in CD8 T cell function. We show that in the absence of ADAP, naïve CD8 T cells exhibit a diminished response to stimulatory Ag, but an enhanced response to weak agonist altered peptide ligands. ADAP-deficient mice exhibit an increased number of MP CD8 T cells that occurs following thymic emigration and is largely T cell intrinsic. Naïve ADAP-deficient CD8 T cells are hyperresponsive to lymphopenia in vivo and exhibit enhanced activation of STAT5 and homeostatic antigen-independent proliferation in response to IL-15. Our results indicate that ADAP dampens naïve CD8 T cell responses to lymphopenia and IL-15, and demonstrates a novel antigen-independent function for ADAP in the suppression of MP CD8 T cell generation.